Human rights and new technologies - Ricoy Casas, Rosa María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Numerous risks have been evidenced not only for data protection, but in general for the fundamental rights of the person such as equality and freedom with the use of numerous technological applications. Ethical biases and dilemmas in the application of artificial intelligence and algorithms, interference in electoral processes or control and social score techniques for political purposes are analyzed. It reflects on the dysfunctions and inequities of many of these new tools for citizenship, and proposes solutions that generate well-being for our democratic societies.